Thalictrum foliolosum DC: An unexplored medicinal herb from north western Himalayas with potential against fungal pathogens and scavenger of reactive oxygen species. (July 2020) - Kumar, Rajeev; Sharma, Nitin; Rolta, Rajan; Lal, Uma Ranjan; Sourirajan, Anuradha; Dev, Kamal; Kumar, Vikas
Abstract: The aim of the present study was to evaluate the antifungal, antioxidant activity and quantification of berberine in different solvent extracts of leaves of Thalictrum foliolosum DC. Cold maceration method was employed for the preparation of extracts using solvents of different polarities (petroleum ether, chloroform, and methanol). Total phenolic content (TPC), total flavonoid content (TFC), antioxidant activity, and antifungal activity of T. foliolosum extracts were investigated using various in vitro assays. A high-performance thin-layer chromatography (HPTLC) method was used for the quantification of berberine. In silico studies confirmed the results of in vitro assays and showed that berberine showed a good binding affinity with cytochrome P450 14 alpha-sterol demethylase (CYP51) (antifungal receptor protein) and human peroxiredoxin 5 (antioxidant receptor). TPC and TFC were highest in methanolic extract. HPTLC quantification of berberine showed a higher amount of berberine in chloroform extract followed by methanol extract). Chloroform extract showed the highest antifungal activity as indicated by a diameter of zone of inhibition and lower minimum inhibitory concentration (MIC) value against fungal strains [ Candida albicans (ATCC90028), C. albicans (MTCC277) and Saccharomyces cerevisiae (H1068)]. Among three extracts, maximum antioxidant activity was shown by chloroform extract as evident from the lowest half-maximal inhibitory concentration ( IC50 ) value with DPPH and FRAP assay. Molecular docking study also showed that berberine interacts strongly with cytochrome P450 14 alpha-sterol demethylase (CYP51) and human peroxiredoxin 5 proteins. Thus, T. foliolosum leaves can be exploited as an alternative source of berberine, with potent antioxidant and antifungal activity. Graphical abstract: Image 1 Highlights: Thalictrum foliolosum DC is a perennial medicinal herb that belongs to the Ranunculaceae family. Comparative HPTLC quantification showed a higher amount of berberine in chloroform extract than other extracts. In silico and in vitro study of berberine from T. foliolosum confer its antioxidant and antifungal property.